PENGARUH PERISTIWA PEMILU LEGISLATIF 2014 TERHADAP PEROLEHAN ABNORMAL RETURN SAHAM LQ 45 DI BURSA EFEK INDONESIA - Mahaputra, I Made Dwi; Purbawangsa, Ida Bagus Anom (E-Jurnal Manajemen, 2015)
This study analyzed the difference of abnormal return and whether the content of the information contained in the LQ - 45 before and after the events would legislative elections in 2014 on April 2 to 16 2014. This study used event study, carried out observations of the average abnormal return for 5 days prior to the event date, and 5 days after the legislative elections of 2014. The data used in this study include the daily closing stock price, stock index . Expected return using a model adapted to the market. The samples used are stocks that are included in the list of LQ - 45 in Indonesia Stock Exchange. Based on the analysis of paired samples t - test showed results that there is no significant difference in abnormal returns before and after the announcement of the 2014 legislative elections events.
Keywords: Abnormal Return, Market Reaction